Language Means for Shaping the Media Image of China in Russian Internet Texts (Case Study of Blogs about the Chinese Opera) - Му, Юйси (Philology & Human, 2021)
The article presents the study of the media image of China in the Russian Internet texts. The purpose of the study is to identify the language means of shaping the media image of China in blogs about Chinese opera. The material involves some of the topical blogs published on the Internet version of «Live Journal» and the «Magazeta». In those materials, the media image of China is partially formed by various aspects of Chinese opera as a cultural phenomenon: it is the cultural context in which Chinese opera exists; features of diverse opera genres; images of performers; audience responses; assessments and feelings of bloggers. The possibilities of expression of different kinds of language means are revealed, so is the authors’ perception of this type of art. It is concluded that the media image created in blogs about Chinese opera by various language means represents China as a country with a long history and unique culture. Chinese opera not only occupies an important place in the world art, but also vividly and meaningfully reflects the mystery of China.